(untitled) (Research, Society and Development, 2023)
Abdominal obesity is a global health concern due to its steadily increasing prevalence. Measures beyond BMI, such as waist circumference, are essential for assessing the risk of diseases related to visceral fat. Alcohol consumption and smoking, along with inadequate dietary habits and physical inactivity, impact the prevalence of obesity and non-communicable diseases. The aim of this study was to analyze the relationship between alcohol consumption and abdominal obesity in university students majoring in health sciences at a university in Pindamonhangaba, SP. Data were collected in person through a questionnaire and waist circumference measurement using a tape measure. One hundred students were analyzed, with 66% (n=66) being female, with an average age of 24 years and an age range of 17 to 40 years. Fifty percent of the participants consumed alcoholic beverages, and 19% had abdominal obesity. Among those who consumed alcohol (n=50), the prevalence of abdominal obesity was 14% (n=7), and the consumption of alcoholic beverages was not considered statistically significant regarding the prevalence of abdominal obesity. In conclusion, although the sample included participants classified with abdominal obesity, the data and variables were inconclusive in determining a relationship between alcohol consumption and the prevalence of abdominal obesity.